Efficient and Flexible Object Sharing - Castro, Miguel; Guedes, Paulo; Sequeira, Manuel; Costa, Manuel (Proceedings of the International Conference on Parallel Processing (ICPP'96), Proceedings of the International Conference on Parallel Processing (ICPP'96), 1996)
DiSOM is a software-based distributed shared memory (DSM) system, which supports intra- and inter-application sharing in heterogeneous networks of multiprocessor workstations. Unlike previous DSM systems, DiSOM provides fine-grained control over communication while retaining a simple shared memory model. It achieves this by using an update-based implementation of entry consistency, semaphores, remote object invocation, dynamic decomposition of objects and object-oriented language mechanisms. These techniques allow programmers to exploit application-specific knowledge to improve performance. A comparison between DiSOM and TreadMarks, a state-of-the-art DSM system, shows that on average DiSOM executes 33% faster, and sends 69% fewer messages and 38% less data.